MEDITATIVE DISCOURSE AS A VARIETY OF AUTHOR’S ESOTHERIC DISCOURSE: STRUCTURAL-PRAGMATIC ASPECT - БУБЛИК, Тетяна (Current Issues of Foreign Philology, 2022)
The article is devoted to the analysis of the structural-pragmatic aspect of meditative discourse. The purpose of our study is to highlight the structural and pragmatic features of meditative discourse as a kind of esoteric discourse. Meditative discourse in its structural and pragmatic aspect has not yet been of interest to linguists, which, in fact, constitutes the novelty of our study. The methodological basis of the work is based on a complex combination of general scientific (induction, deduction), empirical-theoretical (synthesis, analysis) and linguistic methods (pragmatic, contextualinterpretive, etc.). Central in esoteric discourse is the approach to the special worldview of the individual, whose priority is the spiritual meaning of life and the subordination of the phenomena of the material world to higher, invisible manifestations of true being. As a result, meditative discourse is characterized not only by specific themes, but also by structural and stylistic features of construction, which are both a means of pragmatic influence on the addressee. Since the author pursues only one goal – to awaken the reader and encourage self-immersion and self-knowledge, the texts of meditative works are permeated with incentive constructions with a clear pragmatic focus on changing the worldview and priorities of the individual. Motivational constructions are always structured and presented together with repetitions, alliteration/ assonance, enumeration, etc. We can say that the means of syntactic organization of meditative discourse perform both organizational (text-oriented) and pragmatic (reader-oriented) functions, in order to encourage a person to think and contemplate and, accordingly, implement the author’s plan to change the worldview of the addressee. Compiling a scheme that would depict the place of meditative discourse as a subspecies of esoteric discourse in the system of sacred discourses constitutes the perspective of the further research.